Absence of Blood Clotting Substances from Synovial Fluid - Cho, M. H; Neuhaus, O. W (Thrombosis and Haemostasis, 1961)
Analyses were performed on normal bovine synovial fluid for prothrombin, fibrinogen, Ac-globulin (factor V), autoprothrombin I (factor VII), tissue thromboplastin, and antithrombin. None of these active substances in blood clotting was found. The absence of these proteins, especially prothrombin (MW of 62 700), may be on the basis of selective permeability of the capillaries of the synovial membrane to certain plasma proteins.